Efecto de la inclusión de agua en el alimento convencional en cerdos en etapa de levante - Lectong Anchundia, Cristhian Paúl (2021)
The objective was to evaluate the effect of the inclusion of water in the conventional feed in pigs, 24 Landrace breed pigs were used, with a distribution of treatments in a DCA design, these being: T0: inclusion of 0% of water in the feed; T1: inclusion of 25% of water in the food; T2: inclusion of 50% of water in the food. The variables to be measured were: initial, weekly and final weight; weekly and final weight gain; feed conversion; food consumption; dorsal size and chest width; cortisol (stress) tests and weekly weight gain / cortisol levels. The results obtained were: in the final weight (p> 0.05) the T2 stood out (43.85 ± 0.64). Weight gain (p> 0.05), a higher average was obtained at T0 (31.60 ± 0.17). Food consumption (p> 0.05) stood out on T1 (46.15 ± 0.15). While, the final feed conversion (p> 0.05) was T0 (1.45 ± 0.01). In the measurement of dorsal height and chest width (p> 0.05) there was a higher average in T2 (89.75 ± 0.60 and 89.88 ± 0.66). On the other hand, in baseline cortisol levels (p> 0.05), the highest average was highlighted in T0 (15.80 ± 11.49) and in the weight gain / cortisol levels relationship there were atypical data that could be attributed to stress. It is concluded that the inclusion of water in the traditional feed in pigs in the rearing stage does not disfavor the productive variables, however.